Anti‐tumor effects of mAb against l‐type amino acid transporter 1 (LAT1) bound to human and monkey LAT1 with dual avidity modes. Issue 2 (4th January 2019) - Ueda, Shiho; Hayashi, Hidemi; Miyamoto, Takako; Abe, Shinya; Hirai, Kana; Matsukura, Kanji; Yagi, Hideki; Hara, Yuta; Yoshida, Kinji; Okazaki, Shogo; Tamura, Masakazu; Abe, Yuki; et al.
Abstract : l ‐Type amino acid transporter 1 (LAT1) disulfide linked to CD98 heavy chain (hc) is highly expressed in most cancer cells, but weakly expressed in normal cells. In the present study, we developed novel anti‐LAT1 mAbs and showed internalization activity, inhibitory effects of amino acid uptake and cell growth and antibody‐dependent cellular cytotoxicity, as well as in vivo antitumor effects in athymic mice. Furthermore, we examined the reactivity of mAbs with LAT1 of Macaca fascicularis to evaluate possible side‐effects of antihuman LAT1 mAbs in clinical trials. Antihuman LAT1 mAbs reacted with ACHN human and MK.P3 macaca kidney‐derived cells, and this reactivity was significantly decreased by siRNAs against LAT1. Macaca LAT1 cDNA was cloned from MK.P3, and only two amino acid differences between human and macaca LAT1 were seen. RH7777 rat hepatoma and HEK293 human embryonic kidney cells expressing macaca LAT1 were established as stable transfectants, and antihuman LAT1 mAbs were equivalently reactive against transfectants expressing human or macaca LAT1. Dual (high and low) avidity modes were detected in transfectants expressing macaca LAT1, MK.P3, ACHN and HCT116 human colon cancer cells, and KA values were increased by anti‐CD98hc mAb, suggesting anti‐LAT1 mAbs detect an epitope on LAT1‐CD98hc complexes on the cell surface. Based on these results, LAT1 may be a promising anticancer target and Macaca fascicularis can be used in preclinical studies with antihuman LAT1 mAbs. Abstract : Chimeric anti‐LAT1 mAbs showed strong ADCC activity against many human cancer cells from the colon, uterus, lung, and ovary (Figure 4A). Furthermore, the ADCC activity of anti‐LAT1 chimeric mAbs was markedly superior to chimeric anti‐HER1 (Cetuximab) against HCT116 (Figure 4B).